Peran Strategis Widyaiswara Dalam Membangun Kompetensi ASN di Era Digital - Kurniati, Agus (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2022)
The new normal era and the accompanying covid-19 pandemic condition such as digital transformation and the industrial revolution 4.0 which is side by side with 5.0 with VUCA characteristic bring new challenge that demand changes in every line of life. Indonesia is one of the affected countries, so the change are absolutely necessary including the government system. This situation needs an agile government system with online or virtual public management. Digitization is mostly done in the public service sector, including the implementation of State Civil Apparatus competency development, in this process facilitator have a strategic role there. This study discusses the strategic role of facilitator as an integral part of state civil apparatus based on the competency map of facilitator in Regulation of Minister of State Apparatus Empowerement and Bureaucratic Reform Number 42 of 2021 concerning the Functional Position of facilitator juxtaposed with the competency needs in digital era so that widyaiswara can provide a strategic role in developing state civil apparatus competencies. This is a qualitative descriptive research. Data collection use literature study, observation and interview from any sources. From data processing and analysis, it can be concluded that facilitator in carrying out the task in the digital era has its own challenges, so they must be able to apply the principles of innovation, acceleration, efficiency, accountability, inclusion, collaboration, communicativeness and thinking in every decision making. To support the competency development of state civil apparatus, facilitator have important roles including: acting as a center of excellence, strengthening state civil apparatus talent, developing state civil apparatuscompetencies, forming character. A facilitator must be an agile person and open mind and willing to learn new thing according to the demand of the time. This research is expected to provide benefit for the enrichment of knowledge in the field of state civil apparatus competency development, especially in the field of education and training.